(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Chitra Banerjee Divakaruni is an award-winning author and poet. She has been distributed in more than fifty magazines, including the Atlantic month to month and the new Yorkers, and her composing has been incorporated into more than fifty treasuries’. It expounds how those are identified with each other and offers curiosity to her novels. Divakaruni has utilized for the most part dream as a system to extend the magical elements in her novels. Magic realism has the ability to enhance our concept of what is genuine ’by joining all elements of the creative mind, especially as communicated in magic, myth and religion. In magical realism, the essayist stands up to reality and attempts to unwind it, to find what is puzzling in things, throughout everyday life, in human acts. Along these lines, she has mixed magic with realism. She has treated the inanimate things and reptiles, for example, snakes, spices and conch as though they can talk. The writer uses stream of cognizant procedures, dreams and glimmer back methods and other related strategies. The magical elements in her novel demonstrate that they omen reality and it has a connection with brain research moreover. Divakaruni revives the long overlooked Indian myth, conviction, convention, culture and even dreams which are so fundamental for presence, which in reality is just a blend of all in magic realism. In any case, as the novel advances, the dream element decreases and the realistic element ends up conspicuous. As the fundamental point of this paper is to talk about the different novels of Chitra Banerjee Divakaruni. The paper highlights the principle themes of magic realism, myth and culture in Chitra Banerjee Divakaruni’s select novels.